Peran Partisipasi Masyarakat dalam Monitoring dan Evaluasi Dampak Lingkungan Akibat Limbah Industri di Indonesia - Nugraha, Muhammad Haris; Panjaitan, Andrew Alexander; Asshidqi, Muhammad Maulana; Matondang, Ahmad Baihaqie; Solihin, Ikhsan; Situmorang, Marningot Tua Natalis (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This study examines the importance of community participation in monitoring and evaluating the environmental impacts of industrial waste in Indonesia. Rapid industrial growth has led to environmental pollution that threatens health and ecosystems. Although regulations such as the Environmental Impact Assessment (EIA) mandate community involvement, its implementation is often symbolic and ineffective. This study used a literature review with a descriptive qualitative approach. Data were collected from various academic sources and policy reports to understand the forms of community participation, its benefits, and the obstacles encountered. The results show that approaches such as Community-Based Monitoring (CBM) and Citizen Science can empower communities to directly and credibly monitor environmental conditions. This participation has been shown to increase transparency, accountability, and trust among stakeholders. This study confirms that community participation is a crucial element in equitable and sustainable environmental management. To strengthen it, legal support, community capacity building, access to resources, and the use of technology are needed. Participation needs to be transformed from a mere formality into a real force that drives industry towards more responsible practices.